QRIS as a Digital Payment Instrument: Its Impact on People's Financial Behavior in the Industry 5.0 Era - Ahmad Qolyubi; Agus Munandar (Publikasi Indonesia, 2025)
Since its launch by Bank Indonesia in 2019, the Quick Response Code Indonesian Standard (QRIS) has become a key pillar of digital payment systems in Indonesia, accelerating financial digitization and promoting financial inclusion. This study aims to explore the impact of QRIS on public access to digital financial services and its influence on financial behavior. This study adopts a descriptive qualitative approach, collecting secondary data from Bank Indonesia reports, academic journals, previous research, and recent news articles. The findings indicate that QRIS has significantly expanded public access to digital financial services and improved transaction efficiency. However, this convenience also brings varied impacts on financial behavior. On the one hand, QRIS encourages fast and efficient transactions; on the other hand, it may trigger consumerist behavior and reduce saving intentions, particularly among individuals with low financial literacy. Financial literacy plays a crucial role in guiding the wise use of QRIS, those with higher financial understanding tend to utilize QRIS for better money management. In the context of Industry 5.0, which emphasizes sustainability and human-centric development, QRIS presents great potential for enhancing financial well-being. Nevertheless, challenges such as digital literacy gaps, risk of overspending, and the need for adequate infrastructure must be addressed strategically. Therefore, collaboration between policymakers, financial institutions, and the public is essential to foster healthy financial behavior within the rapidly evolving digital ecosystem.